Nitrogen-doped carbon-encapsulated antimony sulfide nanowires enable high rate capability and cyclic stability for sodium-ion batteries - Dong, Yucheng (2021)
Antimony sulfide (Sb2S3) has been employed for materials of the potential anode in sodium-ion batteries (SIBs) because it possesses a high theoretical capacity. However, volume variations coupled with sluggish diffusion kinetics cause rapid capacity degradation and cyclic instability during the sodiation/desodiation process. Here, we introduce a simple strategy to develop nitrogen-doped carbon-encapsulated antimony sulfide nanowire (Sb2S3@N-C) composites for the anode in SIBs. The resulting composites display excellent electrochemical characteristics with remarkable rate capability, ultrahigh capacity, and excellent stability derived from the synergistic effect between a one-dimensional Sb2S3 nanowire and a nitrogen-doped carbon, thus demonstrating the Sb2S3@N-C composites as a material with potential characteristics for the anode in next-generation storage devices. Electrochemical analysis reveals that pseudocapacitive behavior dominates the overall electrochemical process of the Sb2S3@N-C composites, which is responsible for the fast capacitive charge storage.